2001
DOI: 10.1074/jbc.m101531200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Biophysical, and Functional Characterization of Bacterially Expressed and Refolded Receptor Binding Domain ofPlasmodium vivax Duffy-binding Protein

Abstract: Invasion of erythrocytes by malaria parasites is mediated by specific molecular interactions. Plasmodium vivax is completely dependent on interaction with the Duffy blood group antigen to invade human erythrocytes. The P. vivax Duffy-binding protein, which binds the Duffy antigen during invasion, belongs to a family of erythrocyte-binding proteins that also includes Plasmodium falciparum sialic acid binding protein and Plasmodium knowlesi Duffy binding protein. The receptor binding domains of these proteins li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 45 publications
8
109
1
6
Order By: Relevance
“…This is in contrast to a previous study (25) showing that bacterially produced DBL␣ domains were unable to disrupt rosettes. This discrepancy suggests that recombinant proteins produced through denaturation of inclusion bodies may not reflect the correct conformation and that methods to refold the recombinant protein are needed to obtain functional DBL domains (3,33). Recombinant refolded DBL␣ was recognized by plasmas from individuals residing in regions of India and Mozambique with high rates of malaria transmission, indicating that DBL␣ contains B-cell epitopes that are naturally exposed to the host immune system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to a previous study (25) showing that bacterially produced DBL␣ domains were unable to disrupt rosettes. This discrepancy suggests that recombinant proteins produced through denaturation of inclusion bodies may not reflect the correct conformation and that methods to refold the recombinant protein are needed to obtain functional DBL domains (3,33). Recombinant refolded DBL␣ was recognized by plasmas from individuals residing in regions of India and Mozambique with high rates of malaria transmission, indicating that DBL␣ contains B-cell epitopes that are naturally exposed to the host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Bound protein was eluted from the erythrocytes with 300 mM NaCl, separated by SDS-PAGE, and detected by Western blotting using a mouse monoclonal antibody against pentahistidine (Qiagen). Plasmodium vivax region II (PvRII) of the Duffy binding protein, which was previously shown to bind Duffy antigen receptor for chemokines on erythrocytes by this method (33), was used as a positive control. The intensities of the bands were quantified by densitometry scanning.…”
Section: Expression Of Rdbl␣mentioning
confidence: 99%
See 1 more Smart Citation
“…These differences may be due to the type of glycosylation and the extent of glycosylation on molecules produced in the two different expression systems (30). E. coli is thus well suited for the production of nonglycosylated malarial parasite antigens as vaccine candidates (23,28), and in this report we provide the first description of methods developed for refolding and purification of functional E. coli MSP1 42 produced in a bacterial expression system.…”
Section: Discussionmentioning
confidence: 99%
“…29 In addition, different studies suggested that stronger humoral and cellular immune responses to PvDBP-II develop progressively with increasing age, 22,24,29,30 showing a boosting effect that was likely because of repeated exposures to the infection. 28 Also, the anti-PvDBP-II antibodies in populations living in areas endemic for P. vivax could block PvDBP-II ligand DARC-positive erythrocytes 21,31 and inhibit erythrocyte invasion in vitro . 28,32 As shown by several studies, selection of an antigen for vaccination requires a detailed understanding of natural immune responses elicited by the protein from different malariaendemic regions with various epidemiology, and the result of similar studies from one malaria-endemic region cannot be extrapolated to other areas of malaria-endemic regions in the world.…”
Section: Introductionmentioning
confidence: 99%